Indices de competitividad de la producción mexicana de carne de cerdo en el mercado internacional; Competitiveness indices of Mexican pork production in the international market - Miguel Maga\~na Maga\~na; Carlos Leyva Morales; Felipe Alonzo Solís; Edgar Aguilar-Urquizo (Atlantic Review of Economics (ARoEc), 2023)
– The purpose of the work is to assess both the position and tendency of the competitiveness of Mexican pork carcass versus the foreign supply, as well as the relationship between this commercial advantage, the domestic production and exportation thath may a llow proposing strategies to enhance this activity in the medium term. To achieve this goal, the four competitiveness indices postulated by the Inter - American Institute for Cooperation on Agriculture were estimated, and the degree of association between va riables was determined using Pearson s coefficient. It was found that the volume of the primary supply of pork positions Mexico in the fifteenth place worldwide, while as an exporter country it occupies the forty - second place; that the exportation of this meat has as its main destinations the markets of the United States of America and Japan, and that the domestic production has a low level of competitiveness in the international market. It was also found that on the behavior of the production and exportati on of Mexican pork influences factors linked to the particularities of the market and of the commercial process, which determine both productivities, as the generation of exportable surpluses of pork carcass and of value for México s economy.
Keywords: C82; E21; E23; F14; Q11; Q17; 330; Comparative advantage; Foreign market; Domestic supply; Pig farming; Carcass meat